UPAYA MENINGKATKAN MINAT BELAJAR MATEMATIKA MELALUI MODEL MAKE A MATCH PADA SISWA SMP - Sutrisni Sutrisni; Rika Andriani Piliang (Jurnal Dedikasi Pendidikan, 2021)
The low interest of students, especially in mathematics, has long been a burden on the minds of researchers. many students who can not mention the equation of a straight line properly and correctly. In the evaluation, many student scores are below the KKM. Students seem less enthusiastic and not ready to take lessons on straight line equation material so that the class atmosphere becomes passive. This study aims: to determine the application of the make a match model in improving learning outcomes of straight-line equations for grade VIII-3 students in the even semester of SMP Negeri 2 Deli Tua. This research is a classroom action research which consists of two cycles. Each cycle includes planning, implementation, observation and reflection. The subjects of this class action research were students of class VIII-3 even semester of SMP Negeri 2 Deli Tua Kab. Deli Serdang. Based on data analysis, it can be concluded that in cycle 1, students' learning completeness in this material averaged only 69.29, while in cycle 2 by applying the make a match models, the average value increased in cycle 2 to 87.14.